Quercetin Attenuates Ethanol‐Induced Iron Uptake and Myocardial Injury by Regulating the Angiotensin II‐L‐Type Calcium Channel. Issue 5 (19th February 2018) - Guo, Xiaoping; Chen, Man; Zeng, Hongmei; Liu, Peiyi; Zhu, Xinghong; Zhou, Feng; Liu, Jingjing; Zhang, Jun; Dong, Zhuangzhuang; Tang, Yuhan; Gao, Chao; Yao, Ping
Abstract : Scope: Increased iron deposition in the myocardium in alcoholics may lead to increased risk of cardiac dysfunction. Quercetin has been demonstrated to quench production of intracellular free iron‐induced –OH, but the effect of quercetin in ethanol‐induced cardiac damage remains unclear. This study aims to explore whether quercetin attenuates ethanol‐induced iron uptake and myocardial injury by regulating angiotensin II‐L‐type voltage‐dependent Ca2+ channel (Ang II‐LTCC). Methods and results: Adult male C57BL/6J mice are isocalorically pair‐fed either a regular or ethanol‐containing Lieber De Carli liquid diets supplemented with either quercetin (100 mg kg –1  bw) or desferrioxamine mesylate (DFO, 100 mg kg –1 bw) for 15 weeks. Quercetin alleviated ethanol‐induced histopathological changes, creatine kinase isoenzyme release, Ang II secretion, ROS generation, total cardiac iron, and labile iron level. Ethanol exposure or quercetin intervention fails to regulate traditional iron transporters except LTCC. LTCC is upregulated by ethanol and inhibited by quercetin. In H9C2 cell, LTCC is increased by ethanol (100 mm ) and/or Ang II (1 μm ) concomitant with iron disorders and oxidative stress. This effect is partially normalized by quercetin (50 μm ), nifedipine (LTCC inhibitor, 15 μm ), or losartan (Ang II receptor antagonist, 100 μm ). Conclusion: Alcohol‐induced cardiac injury is associated with excessive NTBI uptake mediated by Ang II‐LTCC activation which may be mediated by quercetin against ethanol cardiotoxicity Abstract : Chronic ethanol consumption induces iron overload and subsequently aggravates oxidative stress in cardiomyocytes by Ang II‐LTCC‐pathway, which might be blocked by quercetin through regulating the Ang‐II‐LTCC‐mediated cellular iron uptake.